The Influence of Outdoor Particulate Matter PM2.5 on Indoor Air Quality: The Implementation of a New Assessment Method - Dominik Bekierski; Krystyna Barbara Kostyrko (Energies, 2021)
Epidemiological research has shown that there is a positive correlation between the incidence of disease and mortality in humans and the mass concentration of particulate matter. An average 1 g of suspended dust emitted in a room results in the same exposure as 1 kg emitted to the outside air. In this study, the authors described the state of knowledge on dust pollution inside and outside buildings (I/O ratios), and methods of testing the PM infiltration process parameters. According to the law of indoor–outdoor particle mass balance and the physical basis of aerosol penetration theory, a relatively simple but new method for estimating the penetration factor P was tested. On the basis of the curve of dynamic changes of internal dust concentration in the process of particle concentration decay and next of the followed curve of dynamic rebound of particle concentration, authors measured penetration factor of ambient PM2.5 through building envelope. Authors modification of the method is to be used for determining the value of the particle deposition rate k not from the course of the characteristics in the transient state (the so-called particle concentration decay curves) but from the concentration rebound course, stimulated by natural particle infiltration process. Recognition measurements of the mass concentration of suspended PM2.5 and PM10 particles inside the rooms were carried out. In this study, the choice of the prediction particle penetration factor P calculation method was supported by the exemplary calculation of the p value for a room polluted by PM2.5. The preliminary results of the penetration factors determined by this method P = 0.61 are consistent with the P factor values from the literature obtained so far for this dimensional group of dusts.